Ocular toxoplasmosis with surprisingly good retinal function - Morisbakk, Tove Lise; Lundmark, Per O (Scandinavian Journal of Optometry and Visual Science, 2019)
Ocular toxoplasmosis is an infection in the eye caused by the parasite Toxoplasma Gondii. A common retinal finding in its inactive stages are pigmented retinochoroidal scarring. The retinal function in the affected area assumingly reflects the amount of retinal involvement. This case report presents a 48-year-old woman who has a long-standing large retinochoroidal scar in the temporal posterior pole of her left eye. She had not experienced any visual symptoms, and no recurrent infections had occurred as far as she knew. She has a scotoma in her nasal visual field that her optometrist detected by a coincidence when she was in her twenties. The corresponding visual field defect is smaller and less deep than what may be expected from the structural appearance of the scar. The reported case demonstrates, that the visual function may be well preserved in the visual field corresponding to a retinochoroidal scarred area due to toxoplasmosis, in spite of loss of structures in the outer retinal layers as seen with OCT.